2018
DOI: 10.1042/bcj20180249
|View full text |Cite
|
Sign up to set email alerts
|

Trade-offs with stability modulate innate and mutationally acquired drug resistance in bacterial dihydrofolate reductase enzymes

Abstract: Structural stability is a major constraint on the evolution of protein sequences. However, under strong directional selection, mutations that confer novel phenotypes but compromise structural stability of proteins may be permissible. During the evolution of antibiotic resistance, mutations that confer drug resistance often have pleiotropic effects on the structure and function of antibiotic-target proteins, usually essential metabolic enzymes. In the present study, we show that trimethoprim (TMP)-resistant all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(33 citation statements)
references
References 63 publications
1
30
0
Order By: Relevance
“…This tussle between chaperones and proteases was found to influence the availability of DHFR in bacterial cells and hence to modulate organismal fitness (28). The findings of the present study relate that idea to stability-function trade-offs occurring during the evolution of drug resistance in bacteria, now an established phenomenon (29,31,(46)(47)(48). I propose that destabilization of DHFR due to mutations that confer trimethoprim resistance results in its degradation, presumably by Lon itself, which provides a simple mechanism explaining why certain mutations are able to confer trimethoprim resistance in only Londeficient E. coli.…”
Section: Discussionsupporting
confidence: 51%
See 4 more Smart Citations
“…This tussle between chaperones and proteases was found to influence the availability of DHFR in bacterial cells and hence to modulate organismal fitness (28). The findings of the present study relate that idea to stability-function trade-offs occurring during the evolution of drug resistance in bacteria, now an established phenomenon (29,31,(46)(47)(48). I propose that destabilization of DHFR due to mutations that confer trimethoprim resistance results in its degradation, presumably by Lon itself, which provides a simple mechanism explaining why certain mutations are able to confer trimethoprim resistance in only Londeficient E. coli.…”
Section: Discussionsupporting
confidence: 51%
“…4D). Previous work demonstrated that the Trp30Gly mutation destabilizes DHFR (31). I reasoned, therefore, that the Trp30Gly mutation may render DHFR more prone to proteolysis in Lon-expressing bacteria.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations